Sibling species in the Chrysis ignita complex: molecular, morphological and trophic differentiation of Baltic species, with a description of two new cryptic species (Hymenoptera: Chrysididae). (26th June 2016) - ORLOVSKYTĖ, SVETLANA; BUDRYS, EDUARDAS; BUDRIENĖ, ANNA; RADZEVIČIŪTĖ, RITA; SOON, VILLU
Abstract: Cryptic species complexes cause major challenges for taxonomists and alter understanding of species diversity. In Northern Europe, the Chrysis ignita species group is one such complex with numerous sympatric sibling species. The objective of this paper is to assess the taxonomy of 15 species from this group using three different approaches: molecular, morphological and trophic differentiation. The analysed set of molecular markers included a 7400‐bp‐long sequence of the mitochondrial genome covering complete sequences of CO1, CO2, ATP8, ATP6, CO3, ND3, 16S and 12S rRNA, nine tRNAs and a partial sequence of CytB, as well as a 3880‐bp‐long sequence of the nuclear DNA covering a part of 18S rRNA, the ITS1, 5. 8S rRNA, ITS2 and a part of 28S rRNA. Discrete diagnostic characters of each species sequence were retrieved using the Characteristic Attribute Organisation System algorithm and a molecular identification key was compiled. The study revealed a higher evolutionary rate of the genes ATP8, ATP6, CO3, ND3 and CytB compared to that of CO1, CO2 and 16S ; the studied nuclear markers demonstrated a lower evolutionary rate than the mitochondrial markers. A consensus tree compiled based on the combined mtDNA and nuclear markers with a strongly supported topology resolved the position of the C. schencki – C. parietis sp.n. clade as sister to the C. ignita – C. impressa clade and supported the monophyly of the C. angustula – C. longula clade. We compiled a morphometric species identification key applying linear discriminant equations. The trophic differentiation was assessed using data on host preferences of ten Chrysis species reared from trap‐nests; the analysis demonstrated that most of them are specialists exploiting a single or a few taxonomically related host species. In most cases, all three approaches supported the distinct status of the included species. Moreover, two previously undescribed species were consistently supported by the molecular methods. Therefore, we describe these as new, namely C. horridula sp.n. and C. parietis sp.n. Only C. mediata and C. solida were not clearly distinguished using the molecular phylogeny reconstruction methods. However, based on distinctive niche divergence, the presence of molecular characters and morphometric differences, we consider them as phylogenetically young but distinct species. In view of the weak morphological and molecular differentiation, the widely overlapping distribution areas and often similar habitat preferences and the trophic specialization, the C. ignita complex presents a possible model for studies of sympatric cryptic speciation. This published work has been registered in ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:1EBAF0E1‐5FB7‐4CF4‐A595‐C11982448360 .